Penanganan Bedah Tumor Mammae: Studi terhadap Efektivitas Teknik Onkoplastik dan Konservasi Payudara dalam Menurunkan Morbiditas Pasca Operasi - Rudi Haris Munandar (SENTRI: Jurnal Riset Ilmiah, 2026)
Breast cancer remains one of the most prevalent malignancies globally, prompting continuous refinement of surgical strategies to achieve optimal oncological control while preserving patients’ physical integrity and quality of life. The transition from radical mastectomy toward breast-conserving surgery and oncoplastic approaches reflects a paradigm shift that prioritizes both tumor eradication and postoperative functional–aesthetic outcomes. This study systematically evaluates the effectiveness of oncoplastic and breast-conserving techniques in reducing postoperative morbidity among patients with breast tumors. The research employed a Systematic Literature Review (SLR) guided by the PRISMA framework, focusing on peer-reviewed articles published within the past decade that addressed conservative surgical methods and reported morbidity-related outcomes. From 325 articles initially identified across multiple databases, 75 duplicates were removed, leaving 250 records for title and abstract screening. Subsequently, 125 articles underwent full-text review; 40 were excluded due to inaccessibility, and 55 did not meet the eligibility criteria. Ultimately, 30 studies fulfilled all inclusion requirements and were analyzed comprehensively. The findings indicate that oncoplastic surgery expands the eligibility criteria for breast-conserving procedures without elevating local recurrence rates, while simultaneously improving cosmetic satisfaction and overall quality of life. Conventional breast-conserving surgery combined with radiotherapy demonstrates long-term oncological safety comparable to mastectomy, with added advantages in maintaining body image and psychosocial well-being. Determinants of successful outcomes include anatomical suitability, tumor dimension and topography, surgical expertise, multidisciplinary collaboration, and institutional support systems. Collectively, the evidence underscores that integrative surgical approaches balancing oncological rigor and reconstructive precision contribute significantly to lowering postoperative morbidity.